El juego libre en los sectores y la expresión oral en niños de cinco años en la Institución Educativa Inicial N°705 Las Malvinas Punchana 2024 - Tulumba Panaifo, Pilar (2025)
The objective of this research is to determine the relationship between free play in the sectors and oral expression in five-year-old children from the Initial Educational Institution No. 705 "Las Malvinas" Punchana, 2024. This research chose a quantitative approach, with a relational design and a non-experimental type. The population consisted of 107 five-year-old children from the same institution. In this study, a quantitative approach was adopted, with a relational and non-experimental design. The research population consisted of 107 five-year-old children from the same educational institution. To collect the data, the observation technique was used, employing an observation guide as the instrument, whose validity was confirmed through the evaluation of a panel of experts. The results obtained according to Spearman's correlation coefficient were high (ρ = 0.833) and the significance value was below the threshold of 0.05 (p < 0.05). Therefore, the main hypothesis is accepted: there is a positive and significant relationship between free play in the sectors and children's oral expression. It is concluded that free play in the sectors favors the development of oral expression skills in the children in the sample.